Informing research design through patient and public involvement; patients and carers with lived experience post-hospital discharge and potential roles for general practice pharmacists - Faiza Yahya; Sam Bartlett; Vibhu Paudyal; Muhammad Abdul Hadi; Hamde Nazar; Ian Maidment (BMC Research Notes)
Abstract Background Medication safety across care transitions remains a significant burden on healthcare systems. Patient and Public Involvement (PPI) is useful at the very early stages of intervention development to inform research priorities. The aim of this PPI was to scope patients’ and carers’ lived experiences of medicines management post-hospital discharge to inform the design of a research proposal. Methods A research planning PPI workshop and additional one-to-one discussions were undertaken with patients and informal carers who had experienced a recent discharge from hospital and were prescribed regular repeat medications. Results The 12 public contributors identified that the priority for patients was not limited to medication management alone but rather a broader care package. Multiple themes as priorities for research emerged: (1) broader holistic and social aspects of care involving various healthcare professionals, (2) practical aspects such as timeliness of follow-up and co-ordination of medication management, and (3) communication with the patient/carer and information transfer between settings. Conclusion Valuable insights from this PPI helped inform future research design priorities and identify the need for a more holistic approach to care. Future work with multi-stakeholder engagement involving different professionals across sectors is needed to explore safer integrated transitions of care, as well as the use of ongoing PPI and co-design, considering populations that are most vulnerable.